Penerapan Metode Inside Outside Circle (IOC) dalam Meningkatkan Hasil Belajar Siswa pada Pembelajaran Al Qur’an Hadits di MTs Plus Nurul Ihsan Muktisari Kebumen - Apriliani, Titi; Hilmi, Hilmi; Azhar, Saefudin; Fatimah, Siti; Subarkah, Imam; Maesaroh, Maesaroh; Awanis, Atsmarina (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
The inside outside circle method was first developed by Spencer Kagan (1990). This method allows students to share information at the same time with partners briefly and regularly. This study aims to determine the effectiveness of using the inside outside circle method in improving learning outcomes in learning Al Quran Hadith. The results of this study include student answers to tests given by researchers at the end of learning. The method used in this research is a class action research method (CAR). The research results in cycle I averaged student learning outcomes reaching 71.88 with a percentage of student completeness of 44%, in cycle II the average student learning outcomes reached 74.68 with a percentage of student completeness of 52%, and in cycle III the average the average student learning outcomes reached 74.92 with a student completeness percentage of 56% and in cycle IV the average student learning outcomes reached 76.48 with a 68% student completeness percentage. Based on the increase that has occurred, it can be concluded that the inside outside circle method is effective in improving student learning outcomes in learning Al Quran Hadith. Student learning outcomes will be better if teachers always improve the quality of learning by applying learning methods that can make students more active